Pengaruh Fitur Layanan, Kemudahan dan Efisiensi terhadap Kepuasan Pengguna Aplikasi Muamalat DIN - Khasinta Mazaya Khusna; Novi Khoiriawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of service feature variables, convenience and efficiency on user satisfaction of the Muamalat DIN application in the Tulungagung area. The approach in this study uses a quantitative approach with an associative research type. The population in this study were Muamalat KCP Tulungagung bank customers who used the Muamalat DIN application with a selected sample of 92 people. The sampling technique used accidental sampling. The data analysis used is multiple linear regression analysis. The results showed that the service features variable had no significant effect on user satisfaction while the convenience and efficiency variable had a significant effect on user satisfaction. The test results using the F test show that service features, convenience and efficiency together or simultaneously have a significant effect on user satisfaction with an R square of 67.3%. Keywords: Service Feature; Convenience; Efficiency; User Statisfaction